ИЗУЧЕНИЕ СОВРЕМЕННОЙ ПРАКТИКИ ВОПЛОЩЕНИЯ ИСПОЛНИТЕЛЬСКОГО СТИЛЯ ФОРТЕПИАННОЙ МУЗЫКИ - Ташбаева, Д.Х. (SCIENCE and SOCIETY, 2024)
The article tells about Uzbek fortepiano performing music, peculiarity of its national style. About pianists of Uzbekistan, who feel the instrument in accordance with centuries-old traditions developed in performing on folk instruments and vocal art. Hence the originality of the music of Uzbekistan’s composers, which consists of improvisational and ornamental techniques. Its national uniqueness dictates the pianist’s search for a performing culture that sufficiently reflects the national peculiarity.